Matrilin-3 gene polymorphism in primary knee osteoarthritis: An Evidence based systematic review - Arun Kumar Sharma; Rajbeer Singh; Devendra Singh; Anurag Shukla; Ramesh C Meena; Divyanshu Goyal; Priyanka Sharma; Uday Raman (Asian Journal of Medical Sciences, 2020)
There have been few studies in English literature identifying the potential association and clinical significance of MATN-3 rs8176070 (SNP6) polymorphism in patients with primary knee Osteoarthritis Knee. Objective of this paper was to evaluate the association of matrilin gene-3 and primary osteoarthritis of knee through systematic review of these studies. We did an extensive literature using relevant keywords .3 eligible studies were included for systematic review. Two studies showed significant association, in which Patients with the B\b genotype had worse clinical and radiological findings than those with B\B and b\b genotype. The third study in Indian population did not find any correlation. On the basis of this systematic review we can safely suggest that there is dearth of such studies in literature therefore more of such studies with wider and larger study population shall be undertaken to find Correlation of genetic in this multifactorial disorder and possible cure.